2015
DOI: 10.15171/hpp.2015.025
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Road Traffic Noise on Reaction Time

Abstract: Background: Traffic noise is one of the main important sources in urban noise pollution, which causes various physiological and psychological effects that can cause disturbs in performance, sleep disturbances, hearing loss and impact on job performance. This study was conducted to verify the impact of road traffic noise on reaction time in terms of extraversion and sex. Methods: Traffic noise was measured and recorded in 10 arterial streets in Tehran, and then the recorded noise was emitted towards participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Moreover, according to the results of Jadaan et al (32), traffic noise has a negative effect on workers' and on patient outcomes. Their quiet hours (rest and relaxation) were affected by traffic noise (32,33). The questionnaire in the current study contained a question about recent studies conducted in the Samen area to assess and reduce noise pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, according to the results of Jadaan et al (32), traffic noise has a negative effect on workers' and on patient outcomes. Their quiet hours (rest and relaxation) were affected by traffic noise (32,33). The questionnaire in the current study contained a question about recent studies conducted in the Samen area to assess and reduce noise pollution.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that sound cannot affect function in simple tasks though it can damage short-term memory (35). In complex activities, sound shows further efficiency loss; therefore, it significantly increases in cognitive workload dual tasks that can leave synergistic negative effects (60,61). Sound affects the proper job function by reducing the available cognitive resources, and interferes with the choice of response to environmental stimuli (62,63).…”
Section: Noisementioning
confidence: 99%
“…The problem of traffic noise is one of the factors that affect environmental safety in both developed and developing countries. Research in Tehran, Iran as a developing country shows that traffic noise level affects health especially in psychology (Alimohammad et al, 2015). Previous research showed average noise level of roadside of Makassar City reached 74 dB (Hustim et al, 2011).…”
Section: Introductionmentioning
confidence: 98%